Effect of Molybdenum Trioxide in the Behavior of Poly(vinyl alcohol) Nanocomposites Systems Focusing New Systems for Protection against COVID-19 - Tavares, Maria Inês Bruno; Filho, José Carlos Dutra; Nascimento, Tais; Iulianelli, Gisele Cristina Valle; Merat, Pedro Paulo (Journal of Research Updates in Polymer Science, 2020)
The purpose of this work was to study the molecular dynamics, morphology, mechanical and thermal performance of nanomaterials formed by poly(vinyl alcohol) and molybdenum trioxide (PVA/MoO3) obtained through solution casting method, focusing new materials with therapeutic applications since the molybdenum trioxide exhibit an excellent antibacterial activity and could be a pathway to prevent viruses. The obtaining materials were characterized by conventional techniques as X-ray diffraction, thermogravimetric and dynamical-mechanical analysis. The unconventional low-field NMR relaxometry was used to evaluate the molecular dynamic and morphology of these systems. The results obtained showed that the MoO3 addition into PVA matrix promote an increase on the thermal stability at higher temperatures and a progressive increase on the rigidity of the PVA systems. Also changes in the molecular mobility of nanomaterials determined through the proton spin-lattice relaxation time showed that low proportion of molybdenum trioxide increased the intercalation of the poly(vinyl alcohol) chains between oxide lamellae while higher quantity of molybdenum trioxide caused an inverse effect on the oxide lamellae delamination. From those results the nanomaterials presented a mixed structural organization as intercalated and exfoliated morphologies. According to these first results, the nanocomposites obtained promise to be antimicrobial and antiviral agent to prevent COVID-19 and similar viruses.